Determination of Benzalkonium Chloride in a Disinfectant by UV Spectrophotometry and Gas and High-Performance Liquid Chromatography: Validation, Comparison of Characteristics, and Economic Feasibility - Mariia Smolinska; Roman Ostapiv; Mariia Yurkevych; Liubov Poliuzhyn; Olha Korobova; Ihor Kotsiumbas; Hryhorii Tesliar (International Journal of Analytical Chemistry)
Simple, fast, and validated UV-spectrophotometric, HPLC, and GC methods for the analysis of benzalkonium chloride in a disinfectant were developed. UV-spectrophotometric determination was based on measuring the amount of light absorption of aqueous solutions of benzalkonium chloride at 268 nm. HPLC determination was achieved with a 150 mm × 4.6 mm, 5.0 μm C18 column. The mobile phase consisted of a 0.01% water solution of triethylamine (with pH 2.5) and acetonitrile in the ratio of 40 : 60 v/v. The column temperature was kept at 30°C, and the injection volume was 10 μL. The flow rate was 1.0 mL/min, and the diode array detector was set at 215 nm. GC determination was performed using a flame ionization detector on a glass capillary column ZB-WAX plus 30 m × 0.25 mm with an inner coating thickness of 0.25 μm. It creates a gradient increase in the temperature of the furnace to the maximum of 200°C. The temperature of the injector was 250°C, 1 μl was injected, and the separation of the sample was 1 : 100. Helium was used as a carrier gas, and the gas flow rate was constant, equaling 1.6 ml/min. The temperature of the detector was 250°C, and a mixture of hydrogen, helium, and air in a ratio of 30 : 8.5 : 350 was used in the split of the detector. All proposed methods were validated according to ICH guidelines with respect to the accuracy, precision (interday, intraday, and reproducibility), linearity, the limit of detection, the limit of quantitation, and robustness. All three methods were linear (R2 = 0.997–0.999) over a concentration range of 400–600 μg/ml for UV and 80–120 μg/ml for HPLC and GC, accurate (recovery was 98.4–101.7% for all methods), precise (RSD <2%), and robust. The cost of the analysis of one sample of the disinfectant for the content of benzalkonium chloride by three methods was calculated. The comparison of the obtained results facilitates a more efficient allocation of laboratory resources, depending on the goal.